An essay on real wage index numbers - John H. Pencavel (Institute for the Study of Labor (IZA), 2011)
Real wage index numbers have been used to measure movements in the standard of living of the typical worker. This paper describes some of these indicators for the United States and England. A new real wage index is proposed that resembles the sliding scale used to adjust wages in certain industries years ago. This new index is applied to U.S. manufacturing industry and it suggests a fall in real wages by about 40 percent since 1960. Workers' distributional position in U.S. manufacturing has deteriorated considerably.
urn:nbn:de:101:1-201104113283
Keywords: J31; 330; index numbers; real wages; sliding scale; Reallohn; Lohnstatistik; Industriearbeiter; Lebensstandard; USA